A commentary on the Bible from the Talmud and Hebraica : vol. 2 - Lightfoot, John, 1601-1675 (Peabody, MA Hendrickson, 1989)
Contents : v. 2 : Matthew - Mark. Includes bibliographical references.
Originally "Horae Hebraicae et Talmudicae" in six volumes (1658-1678), published by Oxford UP, 1859.
Keywords: Bible. N.T. -- commentaries